Changing character of cervical cancer in young women. Issue 6669 (4th February 1989) - Elliott, P. M.; Tattersall, M. H.; Coppleson, M.; Russell, P.; Wong, F.; Coates, A. S.; Solomon, H. J.; Bannatyne, P. M.; Atkinson, K. H.; Murray, J. C.
Abstract : To examine the hypothesis that the pattern of cervical cancer is changing data on women presenting with the disease over 34 years were studied retrospectively. During 1953-86, 2628 women with cervical cancer were referred to a large tertiary referral hospital in Sydney; 418 were aged 35 or less. During the period of review the proportion of young women with the disease increased from under 9% in the 1950s and 1960s to about 25% in the 1970s and 1980s; a similar but less pronounced trend was apparent for the whole of New South Wales in the 1970s and 1980s. The prevalence of less common morphological types of cervical cancer increased throughout the period, particularly in the young. Pelvic lymph node metastases were identified in younger patients with stage Ib and IIa tumours more commonly in the later years of the study, suggesting that the disease was becoming more severe. Overall rates of recurrence improved over time, but an apparent increase in early recurrences was observed in young patients with Ib and IIa tumours and without nodal disease. The results suggest that the clinical and pathological behaviour of cervical cancer changed over the period of review.